Effect of serum autoantibodies on the COVID-19 patient’s prognosis - Zhang, Weiming; Tao, Yue; Zhu, Yijia; Zheng, Qisi; Hu, Fenghua; Zhu, Wenbo; Wang, Jian; Ning, Mingzhe (Frontiers in Microbiology, 2023)
Objectives Virus infection closely associated with autoimmune disease. The study aimed to explore the autoantibody profiles and the correlation of autoantibodies with the disease severity and the prognosis of the coronavirus disease 2019 (COVID-19) patients.Methods 337 hospitalized COVID-19 patients from 6th to 23rd January 2023 were enrolled.Logistic and Cox regression analyses were used to analyze the risk factors for the patient's disease severity and outcome. The association between Anti-extractable nuclear antigen antibody (ENA) positivity and the prognosis of COVID-19 patients was analyzed using Kaplan-Meier survival curves.Results 137 of COVID-19 patients were detected positive for antinuclear antibody (ANA), 61 had positive results for ENA, and 38 were positive for ANA and ENA. ANA positivity rate was higher in non-severe illness group (P = 0.032). COVID-19 patients who died during hospitalization had a high rate of ENA positivity than convalescent patients (P = 0.002). Multivariate logistic regression showed that ANA positivity was a protective factor for the disease severity of COVID-19. Multivariate Cox regression analysis revealed that ENA positivity, white blood cells count (WBC), aspartate aminotransferase (AST), Creatinine (CREA), and CRP were independent risk factors for the outcome of COVID-19 patients, and that COVID-19 patients with ENA positivity had a lower cumulative survival rate (P = 0.002).A spectrum of autoantibodies were expressed in COVID-19 patients, among which ANA and ENA positivity was associated with the severity and prognosis of COVID-19. Therefore, autoantibodies may help to assess the disease severity and prognosis of COVID-19 patients.